The Effect of Human Resource Training And Development Programs on Employee Retention - Wegi Aswaya; Altri. Wahida; Samsinar (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The purpose of this study is to explore the training and human resource development program for employee retention at PAM Tirta Mangkaluku, Palopo City. This type of research only uses quantitative methods. Data was obtained through the distribution of questionnaires with a population of 50 employees. The sampling technique used is saturated samples. The number of samples in this study is 50. The measurement instrument uses the Likert scale. Data were processed using SPSS 26. The results of this study are the effect of training programs and human resource development has a simultaneous effect on employee retention, because employees feel accepted by the company, in addition to training and human resource development can improve capabilities, performance, and productivity so that companies can retain potential employees.